PENENTUAN BERAT MOLEKUL DAN DERAJAT POLIMERISASI α – SELULOSA YANG BERASAL DARI ALANG-ALANG (Imperata cylindrica) DENGAN METODE VISKOSITAS - Rudnin Habibah; Darwin Yunus Nasution; Yugia Muis (Saintia Kimia, 2013)
Research of the determination of molecular weight and degree of polymerization α-cellulose from seagegrass (Imperata cylindrica) by viscosity method had been done. To obtain the      α-cellulose, it was done using delignification process. Furthermore, the α-cellulose was characterized by infra red spectrum (FTIR) testing by compared with the infra red spectrum of α-cellulose standard. The α-cellulose viscosity was measured by using Ostwald viscometer and measurement of molecular weight and degree of polymerization based on Mark-Kuhn-Houwink equation. The results showed that the molecular weight and degree of polymerization of the α-cellulose from seagegrass (Imperata cylindrica) were 8.242,7g/mol and 45,8, respectively with the percentage of seagegrass α-cellulose was 45%. Keywords: seagegrass (Imperata cylindrica), viscosity intrinsic, molecular weight, degree of polymerization